2022
DOI: 10.34197/ats-scholar.2022-0004oc
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Language in Letters of Recommendation for Applicants to Pulmonary Critical Care Fellowships

Abstract: Background Previous work has demonstrated letters of recommendation for women in academic medicine are shorter and emphasize communal traits over grindstone or agentic traits. Objective To determine if there are sex-based differences in letters of recommendation written for applicants applying to pulmonary critical care medicine fellowships and if the sex of the letter writer impacts these differences. Methods All fellowship applications subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Historically this work was focused on the gender and URiM status of applicants, examining length of letters, discussions of research, and types of adjectives used by letter writers [ 20 , 30 ]. While more recent work suggests that the trend may be changing for women applicants to PCCM, radiation oncology, and surgery, no work has evaluated the role of letters of recommendation in exacerbating the challenges faced by IMGs as they pursue specialty training and how the language in their letters may hinder them in their pursuits [ 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically this work was focused on the gender and URiM status of applicants, examining length of letters, discussions of research, and types of adjectives used by letter writers [ 20 , 30 ]. While more recent work suggests that the trend may be changing for women applicants to PCCM, radiation oncology, and surgery, no work has evaluated the role of letters of recommendation in exacerbating the challenges faced by IMGs as they pursue specialty training and how the language in their letters may hinder them in their pursuits [ 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown mixed results with women applicants sometimes having longer and more supportive letters as compared to men applicants [ 15 17 ]. Additionally, recent studies have suggested that there may be racial disparities in letters of recommendation with URiM applicants having shorter and less supportive letters of recommendation as compared to applicants who identified as white [ 18 21 ]. However, these studies did not identify differences for IMGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently immersed in the fellowship interview season, I read with interest the article titled “Gendered Language in Letters of Recommendation for Applicants to Pulmonary Critical Care Fellowships” by Viglianti and colleagues ( 1 ). I would like to commend the authors’ efforts to provide an objective analysis of potential biases in the letters of recommendation (LoRs) written for applicants to a pulmonary and critical care medicine fellowship program at a leading university but also comment on the use of imprecise language regarding sex and gender and inquire about possible limitations of their methodology.…”
mentioning
confidence: 99%
“…To explore these important questions, in this issue of ATS Scholar , Viglianti and colleagues ( 2 ) report on a single-center retrospective cohort study using natural language processing techniques ( 3 ) to assess for gender differences in LORs for PCCM applicants. The authors evaluated associations of applicant gender with LOR word count and a composite outcome of supportive word categories (including grindstone terms, agentic terms, research terms, ability terms, and standout terms).…”
mentioning
confidence: 99%